PENGARUH KUALITAS AUDITOR DAN AUDIT TENURE TERHADAP OPINI AUDIT GOING CONCERN SERTA IMPLIKASINYA TERHADAP NILAI PERUSAHAAN - Dewi, Yohana Selvia (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
Abstract     This study aims to empirically examine the effect of auditor quality and audit tenure on going concern audit opinion and its implications for company value. The object of this research is manufacturing industry companies listed on the Indonesia Stock Exchange (IDX) in the period 2015-2018. There are 660 manufacturing industry companies as a population from a predetermined period. The technique used in sampling is to use a purposive sampling method which is then obtained by 72 companies that meet the criteria and can be used as research samples. This study uses secondary data in the form of annual reports obtained from the Indonesia Stock Exchange (IDX). The secondary data obtained were then processed using Statistical Package for Social Sciences (SPSS) software version 22. The analytical method used to test the effect of auditor quality and audit tenure on going concern audit opinion is to use logistic regression analysis, and to test its implications for values The company used multiple linear regression analysis. The results obtained in this study prove that auditor quality does not significantly influence going concern audit opinion, but provides evidence that audit tenure has a significant negative effect on going concern audit opinion. The next thing obtained from the test results is proving that going concern audit opinion does not significantly influence company value. From the three hypotheses proposed in this study it was proven that only one hypothesis was accepted.Keywords: Auditor Quality, Audit Tenure, Going Concern Audit Opinion, Company Value.